Are female business travelers willing to travel during COVID-19? An exploratory study. (July 2021) - Liu-Lastres, Bingjie; Mirehie, Mona; Cecil, Amanda
The outbreak of the COVID-19 pandemic has significantly impacted the tourism industry. A successful recovery from the pandemic requires a clear understanding of the 'new normal', including tourists' perceived risks, safety perceptions, attitudes, and willingness to travel. Guided by the Risk Perception Attitude (RPA) Framework, this study investigated female business travelers' risk perception attitude and willingness to travel in the COVID-19 climate. This study segmented the sample into four distinct RPA groups, including the Avoidance, Proactive, Responsive, and Indifference groups. These groups differ in some demographic characteristics and the strength of willingness to travel. Findings also showed that anxiety, perceived safety, and consumer confidence mediate the relationships between the sample's RPA and willingness to travel, but the exact relationship varies by groups. Finally, this paper discussed the theoretical contributions and practical implications of this study.